Visual outcomes in a series of patients with papilledema and comorbid nutritional deficiency - Spiegelman, Dan V.; Burkland, John; Jameyfield, Evan; Van Stavern, Gregory P.; Stunkel, Leanne (Frontiers in Ophthalmology, 2026)
BackgroundFulminant papilledema is a neuro-ophthalmologic emergency that can lead to permanent vision loss as a result of optic neuropathy. Despite appropriate treatment of intracranial hypertension and improvement of papilledema, some patients continue to experience worsening vision. In some cases, comorbid micronutrient deficiencies, which are an additional cause of optic neuropathy, may contribute to this decline. This case series highlights patients with papilledema whose vision worsened despite improvement in papilledema and who were found to have comorbid nutritional deficiencies.MethodsA retrospective case series of three patients with papilledema were seen between 2019 and 2022 at Washington University in St. Louis and Barnes-Jewish Hospital. All experienced continued vision loss despite successful treatment of intracranial hypertension and were subsequently also diagnosed with nutritional deficiencies. Data on Body Mass Index (BMI), visual acuity, papilledema grade, optical coherence tomography findings, visual fields, and treatment outcomes were analyzed.ResultsThese three female patients had worsening vision despite medical and/or surgical treatment for intracranial hypertension. All were found to have comorbid nutritional deficiencies (thiamine, B12, folate, and/or copper). Following appropriate nutritional supplementation, none experienced continued worsening of their visual function.ConclusionsWorsened vision loss despite papilledema resolution may occur in patients with comorbid nutritional deficiencies. Although we cannot prove a causative relationship with our case series, it may be worth considering screening for micronutrient deficiencies in at-risk patients, as these deficiencies can have visual consequences and are straightforward to treat.